Density Functional Theory (DFT) Study of a Binary Mixture of MBBA and PAA Liquid Crystal for THz Application - Mishra, Mirtunjai; Kumar, Narinder; Singh, Pawan; Rawat, B. S.; Dhyani, Reena; Singh, Devendra; Kumar, Devesh (Makara Journal of Science, 2022)
The present scenario expresses the electro-optical effect of abinary mixture of MBBA and PAA liquid crystal studied under the impact of the electric field in THz frequency. The binary mixture has a negative order parameter, negative birefringence, and a nematic phase stability under such an electric field. The refractive index remains constant at high THz frequency. The director angle is sensitive to THz frequency, contributing to the maximum fluctuation. The atomic contribution of a binary mixture is approximately equal to the molecular contribution. The binary mixture has a remarkably high bandgap. The C-H, O-C, C-N atom stretching, and wagging of alkyl chain contribute to the dipolar strength of the binary mixture.